Dobbs: a not unexpected decision. How we got there and what its future implications are (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Dobbs, the pronouncement that upended 50 years of abortion rights in the United States, has been generally perceived as a totally unexpected decision. Yet, it is since longtime that its germs have been growing underneath. The essay aims to locate where and when the seeds for the overturning of the right to abortion in the United States have been sowed. It, moreover, highlights the future dangers arising from Dobbs on two levels: its possible outreach in terms of further heinous constraints upon women’s reproductive autonomy on one hand, and – on the other hand – the decline of the Supreme Court’s legitimacy to assert its judicial review power looming from it.
Keywords: Dobbs v. Jackson Womens’ Health Organization; abortion rights; Targeted Regulations of Abortion Providers; fetal personhood; SCOTUS’ judicial review legitimacy